A laser additive manufacturing method and application for α-Al₂O₃ thermally grown TiAl-based alloys controlled by a small amount of Si.

CN122746477APending Publication Date: 2026-09-15NANCHANG HANGKONG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610980109.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-02
Publication Date
2026-09-15

Smart Images

  • Figure CN122746477A_ABST
    Figure CN122746477A_ABST
Patent Text Reader

Abstract

The application provides a laser additive preparation method and application of an alpha-Al2O3 thermal growth type TiAl-based alloy based on a small amount of Si regulation. Through the addition and regulation of a small amount of Si element, a single alpha-Al2O3 layer is realized on the surface of the TiAl-based alloy. The ratio of TiAl powder and elemental Si powder in the raw material and the process window of the laser melting deposition technology are disclosed, including key parameters such as laser power, scanning speed and overlap rate. The laser melting deposition technology used in the application is characterized by rapid cooling and non-equilibrium solidification, and the obtained alloy has small grains and is composed of gamma phase and intermetallic compounds. The introduction of a small amount of Si promotes the precipitation of Ti5Si3 phase in the alloy, greatly improving the high-temperature oxidation resistance of the alloy. After a large number of experiments and process parameter optimization, the TiAl-based alloy prepared by the application has a single alpha-Al2O3 layer on the surface and exhibits excellent oxidation resistance and good organizational stability in a high-temperature oxidation environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of additive manufacturing technology for metallic materials, specifically to a laser additive manufacturing method and application of α-Al2O3 thermally grown TiAl-based alloys controlled by a small amount of Si. Background Technology

[0002] TiAl-based alloys possess low density, high specific strength, high specific stiffness, and excellent mechanical properties at medium and high temperatures. They are considered important lightweight high-temperature structural materials to replace nickel-based superalloys and have broad application prospects in fields such as low-pressure turbine blades for aero-engines, turbocharger impellers, and high-temperature structural components. Taking TiAl 4822 alloy as an example, its poor oxidation resistance in high-temperature oxidizing environments (above 800 °C) has become one of the important factors restricting its engineering applications.

[0003] To improve the high-temperature oxidation resistance of TiAl 4822 alloys, scholars both domestically and internationally have conducted extensive research. Many studies have focused on modifying TiAl-based alloys by introducing other alloying elements (such as Mo, Si, and Nb). For example, Mo can reduce oxygen vacancy concentration, Si can form the Ti5Si3 phase, and Nb can inhibit Ti diffusion, thereby promoting Al2O3 formation, improving the density and stability of the oxide film, and thus enhancing the high-temperature oxidation resistance of TiAl 4822 alloys. Additionally, doping with ceramic particles (such as TiB2, TiC, and SiC) can also promote selective Al oxidation and inhibit TiO2 formation. However, current research reports that TiAl 4822 alloys typically form a three-layer structure composed of TiO2, Al2O3, and mixed oxides of the two during high-temperature oxidation, making it difficult to thermally grow a single, continuous α-Al2O3 layer on its surface. Even the few reports of thermally growing α-Al2O3 layers on the surface of TiAl 4822 alloys rely on the formation of a transition layer of a certain thickness on the alloy surface.

[0004] Numerous studies have shown that Si exhibits a strong affinity for Ti in laser-treated molten pools, preferentially precipitating the high-melting-point Ti5Si3 strengthening phase. The Ti5Si3 phase possesses excellent high-temperature stability and oxidation resistance, acting as a diffusion barrier to effectively inhibit oxygen diffusion into the matrix. Simultaneously, Al can partially dissolve in the Ti5Si3 phase, replacing Si sites. During high-temperature oxidation, the surface of the Ti5Si3 phase catalyzes the growth of α-Al2O3, which also has an HCP structure, through the formation of SiO2 with an HCP structure. Furthermore, the precipitation of Ti5Si3 consumes some Ti, further increasing the Al content in the matrix γ-TiAl phase and promoting the selective oxidation of Al, enabling the thermal growth of α-Al2O3 on the γ-TiAl phase surface. Therefore, the introduction of a small amount of Si can improve the high-temperature oxidation resistance of the TiAl 4822 alloy while ensuring that the alloy's mechanical properties remain largely unaffected.

[0005] Because laser melting deposition technology allows for precise control of the deposited layer thickness, this alloy can be deposited as a protective coating on the surface of conventionally cast or smelted TiAl 4822 alloys. Since both the coating and the substrate are based on TiAl 4822 alloy, with the only difference being the Si content, good metallurgical bonding can be achieved, effectively avoiding unfavorable interdiffusion of elements caused by excessive compositional differences.

[0006] Based on this, the TiAl 4822-10Si alloy prepared by laser melting deposition in this invention has excellent high-temperature oxidation resistance. After oxidation in air at 900 ℃ for 20 h, a continuous and single α-Al2O3 layer is thermally grown on the alloy surface. Summary of the Invention

[0007] Based on this, the present invention proposes a laser additive manufacturing method and application for α-Al2O3 thermally grown TiAl-based alloys with controlled small amount of Si. Using laser melting deposition technology, TiAl 4822-xSi alloys are printed on TC4 substrates, resulting in dense and fine-structured TiAl 4822, TiAl 4822-3Si, TiAl 4822-5Si and TiAl 4822-10Si alloys. The small amount of Si content controlled significantly improves the high-temperature oxidation resistance of the alloy without affecting its mechanical properties.

[0008] This invention proposes a laser additive manufacturing method and application for α-Al₂O₃ thermally grown TiAl-based alloys based on a small amount of Si, comprising the following steps: S1. Weigh out different proportions of elemental spherical Si powder and spherical TiAl 4822 alloy powder. The purity of each raw material is greater than 99.9%, and the Si content added to the powder raw materials after mixing is less than or equal to 10 wt.%. S2. The powder raw materials in step S1 are fully mechanically mixed using a ball milling process to obtain spherical alloy powder with an average particle size of 30-50 μm, and the obtained alloy powder is dried in a drying oven at 120 ℃ for 600 min.

[0009] S3. Place the dried alloy powder from step S2 into the powder feeder of the laser melting deposition equipment, and select TC4 titanium alloy as the substrate for depositing TiAl 4822-xSi alloy, and place it horizontally inside the chamber of the laser melting deposition equipment.

[0010] S4. Set the laser melting deposition parameters, start the CNC program, and deposit TiAl 4822-xSi alloy under argon atmosphere protection. Furthermore, in step S1, the Si addition amounts were 3 wt.%, 5 wt.%, and 10 wt.%, respectively, to prepare original alloy powders with four compositions: TiAl4822, TiAl4822-3Si, TiAl4822-5Si, and TiAl4822-10Si.

[0011] Furthermore, in step S3, the TC4 alloy is pre-polished to 1000 grit, then ultrasonically cleaned with alcohol for 10 minutes and dried to remove impurities from the substrate surface.

[0012] Furthermore, the laser melting deposition process parameters in step S4 include: spot size 2 mm, laser power 600-1500 W, scanning speed 500-1200 mm / min, overlap 0.4-0.8 mm, layer thickness 0.15 mm, number of deposition layers 8, and protective gas flow rate 10-18 L / min.

[0013] Furthermore, in step S4, the laser melting deposition employs a serpentine reciprocating scanning strategy, and the scanning direction of the current layer differs from that of the previous layer by 67°. Furthermore, the bulk TiAl 4822-xSi alloy obtained in step S4 has dimensions of 8 mm in length, 8 mm in width, and 5 mm in height.

[0014] Compared with existing technologies, the advantages of this invention are: the laser melting deposition method, characterized by coaxial powder feeding, allows for slight adjustments to the Si content. The deposition process is a rapid cooling non-equilibrium solidification process, resulting in fine alloy grains and an almost entirely γ-TiAl phase. By introducing a small amount of Si without affecting the alloy's mechanical properties, the high-temperature oxidation resistance of the alloy is significantly improved.

[0015] This invention provides a laser additive manufacturing method and application for α-Al2O3 thermally grown TiAl-based alloys based on a small amount of Si. Specifically, it discloses the optimal process parameter window for laser melting deposition manufacturing of TiAl 4822 alloys, including parameters such as spot diameter, laser power, scanning speed, and scanning spacing. Through extensive preliminary experimental research and optimization of relevant processing parameters, the laser additive manufacturing of TiAl 4822-xSi alloys is finally realized. Furthermore, with the increase of Si content, the high-temperature oxidation resistance of the alloy is improved. Attached Figure Description

[0016] Figure 1 SEM images of TiAl 4822-10Si alloy powder after ball milling; Figure 2 XRD pattern of deposited TiAl 4822-xSi alloy; Figure 3 SEM image of deposited TiAl 4822-xSi alloy; Figure 4 The weight gain curve of TiAl 4822-xSi alloy after isothermal oxidation in air at 900 ℃ for 20 h; Figure 5 SEM images of cross-sections of (a) TiAl 4822 and (b) TiAl 4822-10Si alloys after isothermal oxidation in air at 900 ℃ for 20 h. Detailed Implementation

[0017] To facilitate understanding of the present invention, a more detailed description will be provided below with reference to the accompanying drawings. The drawings illustrate preferred embodiments of the invention. However, the present invention can be implemented in many different ways and is not limited to the embodiments described herein. These embodiments are provided to more fully and clearly disclose the content of the present invention.

[0018] See Figures 1-5 This invention provides a laser additive manufacturing method and application for α-Al₂O₃ thermally grown TiAl-based alloys controlled by a small amount of Si, comprising the following steps: S1, weighing spherical TiAl 4822 alloy powder, wherein the purity of the powder raw material is greater than 99.9% and the Si content added in the powder raw material after proportioning is less than or equal to 10 wt.%. S2. The powder raw materials in step S1 are fully mechanically mixed using a ball milling process to obtain spherical alloy powder with an average particle size of 30-50 μm, and the obtained alloy powder is dried in a drying oven at 120 ℃ for 600 min.

[0019] S3. Place the dried alloy powder from step S2 into the powder feeder of the laser melting deposition equipment, and select TC4 titanium alloy as the substrate for depositing TiAl 4822-xSi alloy, and place it horizontally inside the chamber of the laser melting deposition equipment.

[0020] S4. Set the laser melting deposition parameters, start the CNC program, and deposit TiAl 4822-xSi alloy under argon atmosphere protection. Furthermore, in step S1, the Si addition amounts were 3 wt.%, 5 wt.%, and 10 wt.%, respectively, to prepare original alloy powders with four compositions: TiAl4822, TiAl4822-3Si, TiAl4822-5Si, and TiAl4822-10Si.

[0021] Furthermore, in step S3, the TC4 alloy is pre-polished to 1000 grit, then ultrasonically cleaned with alcohol for 10 minutes and dried to remove impurities from the substrate surface.

[0022] Furthermore, the laser melting deposition process parameters in step S4 include: spot size 2 mm, laser power 600-1500 W, scanning speed 500-1200 mm / min, overlap 0.4-0.8 mm, layer thickness 0.15 mm, number of deposition layers 8, and protective gas flow rate 10-18 L / min.

[0023] Furthermore, in step S4, the laser melting deposition employs a serpentine reciprocating scanning strategy, and the scanning direction of the current layer differs from that of the previous layer by 67°. Furthermore, the bulk TiAl 4822-xSi alloy obtained in step S4 has dimensions of 8 mm in length, 8 mm in width, and 5 mm in height.

[0024] This invention provides a laser additive manufacturing method and application for α-Al₂O₃ thermally grown TiAl-based alloys based on a small amount of Si. Specifically, it discloses the optimal process parameters for laser melting deposition to manufacture TiAl 4822-xSi alloys, including: spot diameter, laser power, scanning speed, and scanning spacing. Through extensive preliminary experimental research and optimization of these processing parameters, the laser additive manufacturing of TiAl 4822-xSi alloys was finally achieved. Furthermore, with the increase of Si content, the high-temperature oxidation resistance of the alloy improved.

[0025] Compared with existing technologies, this invention has the following advantages: The laser melting deposition method uses a coaxial powder feeding approach, enabling precise and small-scale control of the Si content. During the deposition process, due to rapid cooling and non-equilibrium solidification characteristics, the alloy microstructure is significantly refined, forming a microstructure consisting almost entirely of the γ-TiAl phase. Based on this, the introduction of a small amount of Si effectively improves the alloy's high-temperature oxidation resistance without significantly affecting its mechanical properties.

[0026] For example, in one embodiment, a method for laser additive manufacturing of high-temperature oxidation-resistant TiAl alloy with a small amount of Si is provided, as detailed below: Example 1 (1) Alloy powder preparation and processing Spherical TiAl 4822 alloy powder with a purity greater than 99.9% and an average particle size of 35.6 μm was weighed and dried in a drying oven at 120 ℃ for 600 min. The dried alloy powder was then placed in the powder feeder of a laser melting deposition equipment.

[0027] (2) Substrate pretreatment TC4 titanium alloy was selected as the substrate for depositing TiAl 4822 alloy. The TC4 titanium alloy was pre-polished to 1000 grit, then ultrasonically cleaned with alcohol for 10 minutes and dried to remove impurities from the substrate surface. The substrate was then placed horizontally inside the laser melting deposition equipment chamber.

[0028] (3) Laser melting deposition of TiAl 4822 alloy The laser melting deposition parameters were set as follows: spot size 2 mm, laser power 800 W, scanning speed 1000 mm / min, overlap 0.4 mm, layer thickness 0.15 mm, number of deposition layers 8, and shielding gas flow rate 18 L / min. The CNC program was started to perform laser melting deposition of TiAl 4822 alloy. (4) Microstructure analysis of the alloy X-ray diffraction and SEM images show that the TiAl 4822 alloy prepared by laser melting deposition consists of TiAl and Ti 0.42 Al 0.58 Two phases constitute, such as Figure 1 As shown, the alloy matrix phase has two contrasts, both being γ-TiAl. The atomic ratio of Ti to Al in the light gray phase is close to 1:1, while the atomic ratio of Ti to Al in the dark gray phase is close to 2:3.

[0029] (5) High-temperature oxidation performance test The weight gain curve of TiAl 4822 alloy prepared by laser melting deposition after isothermal oxidation in air at 900 ℃ for 20 h is shown below. Figure 4As shown, under the same oxidation conditions, the smaller the weight gain of the alloy due to oxidation, the better its oxidation resistance. The cross-sectional morphology of the oxidized TiAl 4822 alloy is shown in the figure. Figure 5 As shown in (a), its surface forms a typical three-layer oxide structure, consisting of a TiO2 layer, an Al2O3 layer, and a mixed oxide layer composed of TiO2 and Al2O3, from the outside to the inside.

[0030] Example 2 (1) Alloy powder preparation and processing Spherical Si powder with a purity greater than 99.9% and spherical TiAl 4822 alloy powder were weighed and mixed. The Si content in the powder raw materials was 10 wt.%. The mixture was then thoroughly mechanically mixed using a ball milling process to obtain spherical alloy powder with an average particle size of 38.4 μm. The obtained alloy powder was then dried in a drying oven at 120 ℃ for 600 min. The dried alloy powder was then placed in the powder feeder of a laser melting deposition system.

[0031] (2) Substrate pretreatment TC4 titanium alloy was selected as the substrate for depositing TiAl 4822-10Si alloy. The TC4 titanium alloy was pre-polished to 1000 mesh, then ultrasonically cleaned with alcohol for 10 minutes and dried to remove impurities from the substrate surface. The substrate was then placed horizontally inside the laser melting deposition equipment chamber.

[0032] (3) Laser melting deposition of TiAl 4822-10Si alloy The laser melting deposition parameters were set as follows: spot size 2 mm, laser power 900 W, scanning speed 1000 mm / min, overlap 0.5 mm, layer thickness 0.15 mm, number of deposition layers 8, and shielding gas flow rate 18 L / min. The CNC program was started to perform laser melting deposition of TiAl 4822-10Si alloy. (4) Microstructure analysis of the alloy X-ray diffraction and SEM images show that the TiAl 4822-10Si alloy prepared by laser melting deposition consists of TiAl and Ti 0.42 Al 0.58 It is composed of three phases, such as Ti5Si3. Figure 1 As shown, the alloy matrix phase has two contrasts, both being γ-TiAl. The atomic ratio of Ti to Al in both the light gray phase and the dark gray phase is close to 2:3, with a slightly higher Al content in the dark gray phase. The white phase is a Ti5Si3 intermetallic compound.

[0033] (5) High-temperature oxidation performance test The weight gain curve of TiAl 4822-10Si alloy prepared by laser melting deposition after isothermal oxidation in air at 900 ℃ for 20 h is shown below. Figure 4 As shown, under the same oxidation conditions, the smaller the weight gain of the alloy due to oxidation, the better its oxidation resistance. TiAl 4822-10Si exhibits the best high-temperature oxidation resistance. The cross-sectional morphology of the oxidized TiAl 4822-10Si alloy is shown in the figure. Figure 5 As shown in (b), a single, continuous Al2O3 layer is formed on its surface.

[0034] The above embodiments are merely preferred embodiments of the present invention, used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Various equivalent substitutions, modifications, alterations, or improvements made to the present invention by those skilled in the art, based on the teachings of the present invention and without departing from the spirit and substance of the present invention, should be covered within the scope of protection defined by the claims of the present invention.

Claims

1. A laser additive manufacturing method and application for α-Al₂O₃ thermally grown TiAl-based alloys controlled by a small amount of Si, wherein the TiAl-based alloys include TiAl 4822, characterized in that... Specifically, the following steps are included: Step 1: Weigh out different proportions of elemental spherical Si powder and spherical TiAl 4822 alloy powder. The purity of each raw material is greater than 99.9% and the Si content added in the powder raw materials after mixing is less than or equal to 10 wt.%. Step 2: The powder raw materials in Step 1 are fully mechanically mixed using a ball milling process to obtain spherical alloy powder with an average particle size of 30-50 μm, and the obtained alloy powder is dried in a drying oven at 120 ℃ for 600 min. Step 3: Place the dried alloy powder from Step 2 into the powder feeder of the laser melting deposition equipment, and select TC4 titanium alloy as the substrate for depositing TiAl 4822-xSi alloy, and place it horizontally inside the chamber of the laser melting deposition equipment. Step 4: Set the laser melting deposition parameters, start the CNC program, and deposit TiAl 4822-xSi alloy under the protection of argon atmosphere.

2. The laser additive manufacturing method and application of α-Al₂O₃ thermally grown TiAl-based alloys based on a small amount of Si as described in claim 1, characterized in that... In step S1, the Si addition amounts were 3 wt.%, 5 wt.%, and 10 wt.%, respectively, to prepare original alloy powders with four compositions: TiAl 4822, TiAl 4822-3Si, TiAl 4822-5Si, and TiAl 4822-10Si.

3. The laser additive manufacturing method and application of α-Al₂O₃ thermally grown TiAl-based alloys based on a small amount of Si as described in claim 1, characterized in that... In step S3, the TC4 alloy is pre-polished to 1000 grit, then ultrasonically cleaned with alcohol for 10 minutes and dried to remove impurities from the substrate surface.

4. The laser additive manufacturing method and application of α-Al₂O₃ thermally grown TiAl-based alloys based on a small amount of Si as described in claim 1, characterized in that... The laser melting deposition process parameters in step S4 include: spot size 2 mm, laser power 600-1500 W, scanning speed 500-1200 mm / min, overlap 0.4-0.8 mm, layer thickness 0.15 mm, number of deposition layers 8, and protective gas flow rate 10-18 L / min.

5. The laser additive manufacturing method and application of α-Al₂O₃ thermally grown TiAl-based alloys based on a small amount of Si as described in claim 4, characterized in that... Laser melting deposition employs a serpentine reciprocating scanning strategy, with the scanning direction of the current layer differing from that of the previous layer by 67°.